PERUBAHAN MASSA AIR, VOLUME, DAN UJI ORGANOLEPTIK KERIPIK BUAH DENGAN BERBAGAI VARIASI WAKTUPADA PENGGORENGAN TEKANAN HAMPA UDARA - Ponno, Yahya Zeth; Sukainah, Andi; Jamaluddin P, Jamaluddin P (Jurnal Pendidikan Teknologi Pertanian, 2016)
The processing of fruits by frying are interesting to be developed. One of the potential fruit processed and fruit chips are developedÂ  papaya (Carica papaya L.). This study aimed to determine changes in water content and volume of papaya chips during frying, and test results hedonic papaya chips. The study was conducted by using the experimental method completely randomized design (CRD) with observation every 15 minutes, for 90 minutes during frying using vacuum fryer. Observations moisture content, volume, and the level of preference (hedonic), performed before and after frying. Analysis of the data by analysis of variance (ANOVA) followed by Tukkey test at 5%. The results showed that the decrease in water content and volume reduction papaya chips tend to stop in a frying for 60 minutes. To test hedonic color and flavor, crispy papaya highly preferred is frying for 60 minutes. As for the hedonic test on the texture, chips are the most preferred frying for 90 minutes